The Influence of Age and Work Tenure on Occupational Burnout among Furniture Industry Workers in Indonesia - Muhammad Basir; Mira Wahyu Kusumawati; Wenny Carsita (LPPM Universitas Harapan Bangsa, 2026)
Occupational burnout has emerged as an important occupational health concern in labor-intensive manufacturing sectors where repetitive physical work and prolonged job demands may increase psychological strain among workers. This study aims to analyze the association between age, work tenure, and burnout levels among furniture production workers from an occupational health and safety perspective. A quantitative analytic study with a cross-sectional design was conducted among 63 workers in a furniture manufacturing unit in Makassar, Indonesia. Data were collected using the Maslach Burnout Inventory (MBI) questionnaire to measure burnout across three dimensions: emotional exhaustion, depersonalization, and reduced personal accomplishment. Age and work tenure were categorized based on sample distribution, and statistical analysis was performed using cross-tabulation and Chi-square tests with a 95% confidence level. The results indicate a significant association between age and burnout level (χ² = 20.746, p < 0.001) as well as between work tenure and burnout level (χ² = 22.828, p < 0.001). Workers in the late-mid adulthood category and those with work tenure exceeding 20 years showed substantially higher proportions of severe burnout compared with younger or less-tenured workers. These findings suggest the presence of cumulative occupational strain resulting from prolonged exposure to repetitive physical labor and workplace stressors. This study highlights the importance of integrating burnout monitoring within occupational health and safety programs. Preventive strategies such as ergonomic improvements, workload management, and job rotation are recommended to reduce burnout risk among long-tenured industrial workers